Which expressions are equivalent to -7+3(-4e-3)
1 answer:
Answer:
The answer is letter A.
-7+3(-4e-3)
−7+3((−4)(2.718282)−3)
=−48.619382
-4(3e+4)
−4((3)(2.718282)+4)
=(−4)((3)(2.718282)+4)
=(−4)((3)(2.718282))+(−4)(4)
=−32.619382−16
=−48.619382
You might be interested in
Answer: x = 5
Explanation:
2•5 = 10
10 + 3 = 13
Hopefully this helps you.
Answer:
200
Step-by-step explanation:
8 * 25
Answer:
-89.41887
Step-by-step explanation:
Answer:
y = 3x + 5
Step-by-step explanation:
add 6x to each side to get:
2y = 6x + 10
finally, divide each side by 2 to get:
y = 3x + 5
Answer:
tanθ = 3/4 p/b
using Pythagoras theorem
H² = P² + b²
H² = 3²+ 4²
H² = 25
H = 5
cosθ = B/H = 4/5